REVIEW OF URBAN GREENING POLICY IN INDONESIA: A CASE STUDY IN JAKARTA PROVINCE - Mohammad Zaini Dahlan; Budi Faisal; Sofia Chaeriyah; Ina Winiastuti Hutriani; Mira Amelia (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2021)
Urban greening schemes in Indonesia have experienced various challenges in providing quality green open space in sufficient quantities and need for a more appropriate scheme. In this case, the policy aspect is presumed to inhibit optimizing the provision and utilization of green open space in Indonesia. This study uses descriptive qualitative method that aims to analyze policy aspects related to the provision of green open space in large and dense urban areas with a case study Jakarta. It provides a basic analysis scheme to find the root cause of the urban greening schemes issue in Indonesia. The result shows that the provision of green open space has been mandated in various regulations and policies on a local to global scales. However, law enforcement efforts in implementing these policies and regulations require integrated and comprehensive endeavors to respond to the complexity of the public policy system related to the provision of green open space. In conclusion, this study needs an in-depth research to find complex and dynamic components associated with the complexity of providing green open space with a dynamic system approach. Keywords: Urban Greening Scheme; Law enforcement, Dynamic complexity